Is sports recreation important to university students? - Andrijašević, Mirna; Ciliga, Dubravka; Jurakić, Danijel (2009)
Abstract: The aim of this research is to examine university students’ attitudes on recreational exercise. The sample included 473 students from the University of Zagreb. We analyzed the data by analysis of frequency and a statistical method called »Relation model of action«. The results indicated that there were two general courses in students’ attitudes on recreation activities. The first course represents general values and the second course reflects the attitudes on specific sports and recreational activities. It can be concluded that university students recognize the importance of exercise but they do not understand its real meaning and they do not exercise regularly. Therefore, it is important to foster positive attitudes towards exercise early in youth, which would allow young people to preserve the healthy habit of exercise throughout their whole life. There is a need for quality system of education, which would start early in childhood
Bibliografija: 16 jed
Sažetak
Keywords: Sportska rekreacija -- Studenti